Lactate minimum, critical velocity, heart rate deflection and 3000m track-tests: relationship to performance and applications for running - Campbell, C. S. G.; Denadai, B. S.; Simoes, H. G. (Book of Abstracts - 9th Annual Congress European College of Sport Science, July 3-6, 2004, Clermont-Ferrand, France, 2004)
and noninvasive methods have been proposed. Conconi et al. suggested the running velocity associated to the heart rate deflection (VHRd) as a noninvasive method to predict the aerobic-anaerobic transition (Trans). Tegtbur et al. proposed a lactate minimum field test to evaluate the aerobic fitness of runners and basketball players on running. Comparative studies of lactate minimum to other exercise testing protocols have been conducted. Simoes et al. verified no differences and high correlation between Vlm and the running velocities associated both to the individual anaerobic threshold and onset of blood lactate accumulation. The Critical Velocity (CV) identification is a non-invasive protocol that has been proposed for aerobic evaluation, to predict endurance performance and is sensitive to training adaptations. CV was believed to be an exercise intensity that relies exclusively on aerobic sources and thus can be sustained during long period of time without fatigue. Also, CV is suppose to represent the upper limit of sustainable exercise intensity (Hill et al. 2002). The present study compared the running velocities associated to lactate minimum (Vlm), heart rate deflection (VHRd), critical velocity (CV), 3000m (V3000) and 10000m performance (V10km). Additionally the ability of Vlm and VHRd on identifying sustainable velocities was investigated. Methods Twenty endurance runners (28.5 +/-5.9yr.) performed the following tests: 1) 3000m running test for V3000. 2) An all-out 500m sprint followed by 6x800m incremental bouts with blood lactate ([lac]) measurements for Vlm. 3) A continuous velocity-incremented test with heart rate measurements at each 200m identified the VHRd. 4) Participants attempted to 30min running both at Vlm(ETVlm) and VHRd(ETVHRd). The distance-time and velocity-1/time relationships produced CV results by two (500m and 3000m) or three predictive trials (500m, 3000m and distance reached before exhaustion during ETVHRd). A pedestrian 10km race was recorded for V10km. Results The CV identified by different methods did not differ from each other. The results (m.min-1) revealed that Vlm (281.0 +/-14.8) < CV (292.1+17.5) . V10km (291.7+19.3) < VHRd (300.8+18.7) . V3000 (304.0+17.5) with high correlation among parameters (p<0.001; Table I). During ETVlm a 30min running was completed while during ETVHRd athletes lasted only 12.5 +/-8.2min with increasing [lac]. Discussion/Conclusions The CV and Vlm track-protocols are valid for running evaluation and performance prediction and the parameters studied have different meaning. The Vlm may reflect the moderate-high intensity domain (below CV), can be sustained without [lac] accumulation and may be used for long-term exercise prescription while the VHRd overestimates a running intensity that can be sustained for long-time and that both V3000 and VHRd reflect the severe intensity domain (above CV).